TEACHING ENGLISH THROUGH ENGLISH MOVIE: ADVANTAGES AND DISADVANTAGES - Armilia Sari; Bastian Sugandi (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2015)
Abstract: Technological advances in globalization era demand all English teachers to be more creative and innovative in using instructional media. Movie or film is one of audio-visual media that teachers can use to improve students‟ English skills. There are some advantages of using English movie in English teaching. For example, movie can keep students‟ interest in learning English, movie can improve student‟s listening and speaking skills, and movie can improve student‟s pronunciation and vocabulary. However, teaching English through English movie also has some bad effects or disadvantages. For example, it takes long time to watch a movie so that students may get bored, students prefer watching actors or actresses to focusing on the main instructional goal, fiction movie can cause students think and imagine something illogically, and movie can cause students imitate bad scenes from the actors or actresses. To overcome the bad impacts of movie, English teachers should consider some solutions. For example, teachers should use short English movie to save time in learning, teachers should always remind students the main instructional goal before and after watching the movie, teachers should control student‟s thinking, imagination, and emotional, and teachers should select a good educational English movie.Key words: Teaching English through movie, advantages, disadvantages